Pengembangan Multimedia Interaktif Objek Wisata Nusa Penida dengan Metode Multimedia Development Life Cycle (MDLC) - Kopriyanto; Tangguh Widodo; Shahnaz Ferdiansyah; Mario Rudy Silalahi (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2024)
Nusa Penida is a natural tourist destination that attracts many tourists. However, there is a problem: the lack of interactive and interesting multimedia-based information about Nusa Penida. As a result, visitors do not get an in-depth and informative experience about this tourist spot. Therefore, information media is needed that can present information interestingly and interactively to improve the tourist experience. This research aims to develop information media that can provide visitors with an interesting and in-depth understanding of the attractions of Nusa Penida through interactive multimedia. The method used in developing interactive multimedia is the Multimedia Development Life Cycle (MDLC), which includes the stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. The research results show that the existing features can be used well, according to the results of the alpha testing. The feasibility of this interactive multimedia was also proven through beta testing carried out by 31 respondents, with a rating of 4.69 out of 5, indicating that this information media is suitable for use.